Value of Pathology Review in a Population-based Series of Ovarian Tumors - Stewart, C.; Stewart, Louise; Holman, C.; Jordan, S.; Semmens, James; Spilsbury, Katrina; Threlfall, T. (2016)
Ovarian neoplasia comprises a heterogenous group of tumors with distinct clinicopathologic and molecular features and therefore assessment of potential risk factors should be tumor subtype specific. As part of ongoing epidemiological investigations of ovarian neoplasia in Western Australia, we performed an initial review of original pathology reports followed, in selected cases, by reassessment of histology material to optimize accurate diagnosis. Additional immunohistochemistry, often using antibodies unavailable at the time of initial assessment, was also performed as required. From an initial cohort of 1660 cases identified through the Western Australia Cancer Registry, benign, nonepithelial, nonovarian, miscellaneous, and indeterminate cases were excluded. Also excluded were 33 cases that were reclassified as ovarian metastases rather than primary ovarian tumors. Following exclusions there remained 1321 borderline and malignant epithelial neoplasms. The diagnosis was considered accurate in 1186 cases (89.8%) based upon information in the initial pathology reports and clinical follow-up data but uncertain in 135 cases (10.2%). Histologic review was possible in 92 of the latter tumors leading to an amended diagnosis in 63 cases (68.5%). The most common types of diagnostic amendment were the reclassification of high-grade carcinomas of undifferentiated, endometrioid, or transitional appearance as high-grade serous carcinoma, and the reclassification of most carcinomas of mixed epithelial type as “pure” carcinomas. This review illustrated specific pitfalls in the diagnosis of ovarian epithelial neoplasia and helped to maintain the accuracy of the Western Australia Cancer Registry. Accurate diagnosis will optimize further epidemiological studies assessing risk factors in specific subtypes of ovarian neoplasia.